Cycloartane-3,24,25-triol inhibits MRCKa kinase and demonstrates promising anti prostate cancer activity in vitro - Lowe, Henry I C; Watson, Charah T; Badal, Simone; Toyang, Ngeh J; Bryant, Joseph (My University, 2012)
Abstract Background Given the high occurrence of prostate cancer worldwide and one of the major sources of the discovery of new lead molecules being medicinal plants, this research undertook to investigate the possible anti-cancer activity of two natural cycloartanes; cycloartane-3,24,25-diol (extracted in our lab from Tillandsia recurvata) and cycloartane-3,24,25-triol (purchased). The inhibition of MRCKand#945; kinase has emerged as a potential solution to restoring the tight regulation of normal cellular growth, the loss of which leads to cancer cell formation. Methods Kinase inhibition was investigated using competition binding (to the ATP sites) assays which have been previously established and authenticated and cell proliferation was measured using the WST-1 assay. Results Cycloartane-3,24,25-triol demonstrated strong selectivity towards the MRCKand#945; kinase with a Kd50 of 0.26 and#956;M from a total of 451 kinases investigated. Cycloartane-3,24,25-triol reduced the viability of PC-3 and DU145 cell lines with IC50 values of 2.226and#8201;and#177;and#8201;0.28 and#956;M and 1.67and#8201;and#177;and#8201;0.18 and#956;M respectively. Conclusions These results will prove useful in drug discovery as Cycloartane-3,24,25-triol has shown potential for development as an anti-cancer agent against prostate cancer.